Vitamin D Status Is Not Associated with Cognitive or Motor Function in Pre-School Ugandan Children - Mutua, AM; Nampijja, M; Elliott, AM; Pettifor, JM; Williams, TN; Abubakar, A; Webb, EL; Atkinson, SH (MDPI, 2020)
Vitamin D deficiency is common worldwide and young children are among the most affected groups. Animal studies suggest a key role for vitamin D in brain development. However, studies investigating the effects of vitamin D on neurobehavioural outcomes in children are inconclusive and evidence is limited in sub-Saharan Africa. We evaluated the effect of vitamin D status on cognitive and motor outcomes using prospective data from the Entebbe Mother and Baby Study birth cohort. We analysed data from 302 Ugandan children with 25-hydroxyvitamin D (25(OH)D) measurements below five years and developmental measures at five years of age. We used multivariable linear regression, adjusted for potential confounders, to estimate the effect of 25(OH)D on cognitive and motor outcomes. Of 302 children, eight (2.7%) had 25(OH)D levels <50 nmol/L, 105 (35.8%) had levels 50–75 nmol/L and 189 (62.6%) had levels >75 nmol/L. There was no evidence that earlier vitamin D status was associated with cognitive and motor outcomes in five-year-old Ugandan children. This study adds to the sparse literature and highlights the need for further longitudinal studies on vitamin D and neurobehavioural outcomes in children living in sub-Saharan Africa.